1996
DOI: 10.1073/pnas.93.4.1418
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five coregulated transcripts define a sterigmatocystin gene cluster in Aspergillus nidulans.

Abstract: Sterigmatocystin (ST)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
395
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(402 citation statements)
references
References 66 publications
4
395
0
3
Order By: Relevance
“…Moreover, the fluG 1 DsfgA, DfluG sfgA50, and DfluG DsfgA mutants accumulated brlA mRNA as early as 18 hr in liquid submerged culture (not shown). Finally, the DfluG DsfgA mutant regained the ability to produce ST and restored the expression of ST-specific genes (Brown et al 1996) at wild-type levels (not shown). These results indicate that SfgA plays a key role in negative regulation of conidiation and ST production, and that the primary role of FluG is to remove SfgA-mediated repression of conidiation.…”
Section: H48qv49fmentioning
confidence: 99%
“…Moreover, the fluG 1 DsfgA, DfluG sfgA50, and DfluG DsfgA mutants accumulated brlA mRNA as early as 18 hr in liquid submerged culture (not shown). Finally, the DfluG DsfgA mutant regained the ability to produce ST and restored the expression of ST-specific genes (Brown et al 1996) at wild-type levels (not shown). These results indicate that SfgA plays a key role in negative regulation of conidiation and ST production, and that the primary role of FluG is to remove SfgA-mediated repression of conidiation.…”
Section: H48qv49fmentioning
confidence: 99%
“…19 Clusters of fungal biosynthetic genes have also been found for biosynthetic processes of sterigmatocystin formation by Aspergillus nidulans. 20 Antibiotic formation usually occurs during the late growth phase of the producing microorganism. The temporal nature of their formation is certainly genetic, but expression can be influenced greatly by environmental manipulations.…”
Section: Introductionmentioning
confidence: 99%
“…Although these genes have been shown to have independent promoter sequences it is possible that other cis-acting sequences independently co-regulate their expression. Functionally-related colocalised genes are often transcriptionally co-regulated and this may be due to common enhancer sequences that bind particular transcription factors (Brown et al, 1993;Colombo et al, 1992; GoÈ decke et al, 1991; Jones et al, 1995). If the enhancer sequence on each chromosome is identical then the alleles of both genes would express equally well and this was the case in the majority of individuals we tested.…”
Section: Discussionmentioning
confidence: 91%